HUBUNGAN KONFLIK PERAN GANDA DAN TINGKAT STRESS DENGAN BURNOUT SYNDROME PADA KELUARGA DI KELURAHAN BAHAGIA SELAMA MASA PANDEMI COVID-19 - Widhi Nurfadillah, (2022)
The condition of burnout syndrome is prone to occur in older people, especially during the COVID-19 pandemic. The unpreparedness of parents, especially those who work with multiple roles that appear suddenly will lead to dual role conflicts. Conflicts that occur trigger the emergence of stress experienced and if it occurs for too long it will cause burnout syndrome conditions which will have an impact on the physical and emotional conditions of individuals. This study aims to analyze the relationship between Multiple Role Conflict and Stress with Burnout in parents. This study used measuring instruments Depression Anxiety Stress Scale (DASS42), Maslach Burnout Inventory (MBI) and Work and Family Conflict Scale (WAFCS) with a Cross Sectional research design and Chi Square statistical test with 95% CI using random sampling technique as many as 220 respondents. in the Happy Village. The chi-square test shows that there is a dual role conflict with a burnout (p value of 0.012) and stress with a burnout (p value of 0.035), which can be concluded that there is a relationship between multiple role conflict and stress with burnout syndrome. It is suggested that parents can avoid stress that comes from multiple roles so that burnout syndrome does not occur.